DISRUPSI EKONOMI KAITANNYA DENGAN START UP DI INDONESIA - Tumiar Berthalina Simatupang, S.I.Kom, M.I.Kom, Tumiar Berthalina Simatupang, S.I.Kom, M.I.Kom (Akademi Komunikasi SAE Indonesia, 2023)
What is meant by the term Economic Disruption? And what does this have to do with start-ups that are already very developed in Indonesia today? And what is the start-up itself? There are still many questions related to today's businesses? Why can this type of business compete with big businesses in Indonesia today? In the era of industry 4.0, all of which are digital eras, many new start-ups have emerged. Where the role of start-ups is needed at this time, namely during a pandemic situation or a stay at home situation. But the emergence of new start-ups also has two sides, namely the side of success so that it is able to generate profits and also the side of failure that causes many losses. The question here is why it works and what influences it? And why do others fail, and what contributed to those failures? The above questions will be explained in detail in this journal. This research focuses on research in the field of economics and also the field of human resources where these two things are the key to success in a business. This research focuses on HR and finance research. And it is hoped that it can be an input for the success of start-ups, especially in the field of Creative Media.